UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKN) MELALUI METODE INQUIRI DI KELAS III SD NEGERI 168060 KOTA TEBING TINGGI - Merlin Simangunsong (PGSD Universitas Negeri Medan, 2018)
This Classroom Action Research aims to improve PKn learning outcomes of class III students by using the Inquiri Method The study was conducted at the 168060 Public Elementary School in Tebing Tinggi City. With the subject of the action of 1 teacher and the recipient of the action are class III students totaling 35 people. This research was conducted in 2 cycles, each cycle using procedures, namely planning, implementing actions, observing and reflecting. The hypothesis in PTK is: Through the application of the Cooperative learning model with the inquiry method, the learning achievements of class III students in PKn subjects can be improved. The evaluation results prove that after the first cycle of action the learning outcomes of new students reach 54.28% with an average of 64.62 while the second cycle reaches 85.71% with an average of 75.71 while the percentage of student activity in the first cycle reaches 50 , 86%, overall the second cycle increased by 43.75% with attainment of 94.61%.Keywords: Inquri Method, Learning Outcomes, Student Activity Increases